2005
DOI: 10.1080/15287390590909715
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers (PBDEs) In U.S. Computers and Domestic Carpet Vacuuming: Possible Sources of Human Exposure

Abstract: Polybrominated diphenyl ethers (PBDEs), a type of brominated flame retardant chemically and toxicologically similar to polychlorinated biphenyls (PCBs), are a class of emerging environmental and human contaminants. They have recently been detected in U.S. milk, blood, and food at the highest levels in the world. This pilot study was undertaken with the aim of determining levels of PBDE in the U.S. indoor environment, to assess the potential exposure to PBDEs from computer surfaces and carpets. Food of animal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 58 publications
4
51
3
Order By: Relevance
“…A clear clustering of samples was also observed, showing that BDE-209 is indeed the dominant contaminant in Beijing. Deca-BDE mixture is the most widely used commercial mixture, and comprises 97% BDE-209 (Schecter et al 2005). This is consistent with the prevalent use of deca-BDE as a flame retardant in Beijing.…”
Section: Resultssupporting
confidence: 49%
“…A clear clustering of samples was also observed, showing that BDE-209 is indeed the dominant contaminant in Beijing. Deca-BDE mixture is the most widely used commercial mixture, and comprises 97% BDE-209 (Schecter et al 2005). This is consistent with the prevalent use of deca-BDE as a flame retardant in Beijing.…”
Section: Resultssupporting
confidence: 49%
“…Although PBDE contamination of food is currently higher in the USA than in other countries, diet alone cannot explain the higher levels of PBDEs in the general U.S. population (Jones-Otazo et al 2005;Wilford et al 2005;Schecter et al 2006a;Fischer et al 2006;Lorber, 2007). Several studies have indicated that house dust is a major source of exposure to PBDEs (Jones-Otazo et al 2005;Schecter et al 2005b;Wu et al 2007). For toddlers in particular, dust has been estimated to account for 80% to 93% of PBDE exposure .…”
Section: Human Exposure and Body Burdenmentioning
confidence: 99%
“…The total concentration (sum of the nine congeners) averaged 8154 ng/g dwt, which is about two orders of magnitude higher than the outdoor total soil concentration. Other US studies included one measuring 16 homes in the District of Columbia and one in Charleston, SC, with an average total concentration of 5,900 ng/g dwt (Stapleton et al, 2005), one measuring 20 homes in Boston, MA; with geometric mean concentrations from three locations (living room, bedroom, and vacuum dust) of 6332, 13,882, and 4213 ng/g dwt (Webster, 2006), one in Texas, where the median and mean from nine samples were 2507 and 12,136 ng/g dwt, respectively (Schecter et al, 2005a), and a few others where BDE 209 was not measured. Studies outside of North America tended to show significantly lower dust concentrations.…”
Section: Exposure Media Concentrationsmentioning
confidence: 99%